2019
DOI: 10.1177/1744629519831566
|View full text |Cite
|
Sign up to set email alerts
|

Connectedness and ICT: Opening the door to possibilities for people with intellectual disabilities

Abstract: This study aimed to investigate the experiences of people with intellectual disability (ID) using information and communication technologies (ICTs) and the ways these technologies foster social connectedness. In partnership with a community mental health organization, this qualitative descriptive study explored the experiences of 10 people with ID using ICTs. Participants described how ICTs Opened the Door to Possibilities in their life – ICTs provided an avenue for connecting with other people, a means to pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 43 publications
6
54
0
1
Order By: Relevance
“…Barlott et al . 2019a; Werner and Shpigelman 2019; Seale and Chadwick 2017) over‐reporting the beneficial effects of ICTs for people with ID, leading to a push towards digital inclusion practices focused on providing access to technology. This represents the enchantment of technology, whereby the goodness of technology is the normative starting point.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Barlott et al . 2019a; Werner and Shpigelman 2019; Seale and Chadwick 2017) over‐reporting the beneficial effects of ICTs for people with ID, leading to a push towards digital inclusion practices focused on providing access to technology. This represents the enchantment of technology, whereby the goodness of technology is the normative starting point.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilises data collected from previous research by one of the authors (TB) that explored experiences of people with ID in relation to ICT use (Barlott et al . 2019a). These researchers descriptively analysed interviews with people with ID and concluded that ICTs created opportunities for connecting with others, pursuing interests and organising everyday life – the authors explored how technology had the potential to enhance agency and self‐determination in the lives of participants.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations